Democratic Republic of Timor-Leste : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Democratic Republic of Timor-Leste. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation on Timor-Leste highlights that the Timorese economy has posted high economic growth over the past two years, driven by rapid increases in government spending and a recovery in agriculture from a 2007 drought. Central government spending rose sharply in 2008, reflecting efforts to address pressing development needs and secure social cohesion. Executive Directors have welcomed the recently announced moderation in government spending. Directors have also supported the prudent approach toward widening the fund's investment portfolio.